2005
DOI: 10.1002/pbc.20392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of telomerase activity and RNA expression in a patient with acute promyelocytic leukemia treated with all‐trans retinoic acid

Abstract: In this study, we show that all-trans retinoic acid (ATRA) treatment leads to a rapid decrease in telomerase activity, which was associated with the reduction in myeloblasts and occurs before the appearance of myelocytes, in a patient with acute promyelocytic leukemia (APL). Microarray analysis by ATRA treatment for 48 hr in peripheral blood mononuclear cells (in vivo) and in cultured bone marrow mononuclear cells (in vitro) from a patient with APL revealed upregulation of CD11b, CD11c, CCAAT enhancer binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All‐ trans retinoic acid may also exert its effects via a non‐receptor pathway by activating nuclear factors, such as C/EBP 11–16 . Because the JWA proximal promoter region does not contain RARE but does contains two CCAAT boxes, which C/EBP may bind to, the expression of JWA may be mediated by ATRA‐ activated C/EBP, which binds to CCAAT boxes of the JWA promoter, and this may critical for the antiproliferation and pro‐apoptosis role of ATRA; however, direct evidence of this needs to be provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All‐ trans retinoic acid may also exert its effects via a non‐receptor pathway by activating nuclear factors, such as C/EBP 11–16 . Because the JWA proximal promoter region does not contain RARE but does contains two CCAAT boxes, which C/EBP may bind to, the expression of JWA may be mediated by ATRA‐ activated C/EBP, which binds to CCAAT boxes of the JWA promoter, and this may critical for the antiproliferation and pro‐apoptosis role of ATRA; however, direct evidence of this needs to be provided.…”
Section: Discussionmentioning
confidence: 99%
“…The RAR and RXR modulate the expression of target genes by interacting as either homodimers or heterodimers with the retinoic acid response element (RARE) located in the promoter regions of target genes 10 . Furthermore, ATRA may also exert its effects via a non‐receptor pathway by activating nuclear factors, such as the CCAAT/enhancer binding proteins (C/EBP) 11–14 . It had been shown that C/EBPα is involved in the activation of Hp gene expression by ATRA in human monocytic cells 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the terminal maturation of tumor cells is associated with the repression of telomerase activity [14,15], which has also been confirmed in leukemia [25,26]. In APL, ATRA treatment leads to a rapid decrease in telomerase activity both in the primary cell and the cell line with two pathways, the RAR3-dependent and RXR3-dependent pathways [27,28], and we further found that it was TANK1, not TANK2, that positively regulates telomerase activity, and that Pinx1 expression may also be involved [29]. In this study, we found that the relative telomerase activity of NB4-LR1 cells was significantly higher than that of NB4 cells, and the treatment of ATRA can reduce the level as remarkably as in NB4 cells.…”
mentioning
confidence: 80%
“…Although the A 260 /A 280 ratios of the RNA in FFOE BM was 1.71 ± 0.06, which is slightly lower than that of fresh BM, the RNA quality was good enough to obtain 28s and 18s rRNA bands and enabled RT-PCR for BCR-ABL fusion transcript to be performed. Well-preserved DNA and RNA is critically important for the research of haematological malignancies (Florell et al, 2001;Thö rn et al, 2005;Akiyama et al, 2006), because mutations or over-expressions of specific genes may be of diagnostic (Kang et al, 2002) or prognostic importance (Shanafelt, Geyer & Kay, 2004;Tallman, Gilliland & Rowe, 2005).…”
Section: Discussionmentioning
confidence: 99%